Risk factors for extended-spectrum b-lactamases-producing Escherichia coli urinary tract infections in a tertiary hospital - María Dolores Alcántar-Curiel; Celia Mercedes Alpuche-Aranda; Héctor Javier Varona-Bobadilla; Catalina Gayosso-Vázquez; Ma. Dolores Jarillo-Quijada; Mauricio Frías-Mendivil; Lucio Sanjuan-Padrón; José Ignacio Santos-Preciado (Instituto Nacional de Salud Pública, 2015)
Objective. To assess the risks factors for urinary tract infections (UTIs) caused by Extended-Spectrum Beta-Lactamases (ESBLs)-producing E. coli and the molecular characterization of ESBLs. Materials and methods. A case-control study was performed to identify risk factors in consecutively recruited patients with UTIs caused by ESBLs or non-ESBLs-producing E. coli in a tertiary hospital in Mexico. Results. ESBLs-producing E. coli were isolated from 22/70 (31%) patients with E. coli UTIs over a three month period. All isolates were resistant to cephalosporins and quinolones but susceptible to carbapenems, amikacin and nitrofurantoin. Prior antibiotic treatment with more than two antibiotic families (OR=6.86; 95%CI 1.06-157.70; p=0.028), recurrent symptomatic UTIs (OR=5.60; 95%CI 1.88-17.87; p=0.001) and previous hospitalization (OR=5.06; 95%CI 1.64-17.69;p=0.002) were significant risk factors. Sixteen isolates harbored the beta-lactamase (bla)CTX-M-15 gene and five the blaTEM-1 gene. Conclusions. One of every three patients presented UTIs with ESBLs-producing beta-lactams and fluoroquinolone resistant E. coli. Risk factors and resistance patterns must be taken into account for developing antibiotic use policies in these settings